Quality of Life Framed by Local Wisdom: A Case Study of the Indigenous Communities of Pulo Garut, Naga Tasikmalaya, and Kuta Ciamis - Indah Khoirunnisa Tosin; Hari Rudiana; Eriwan Edna Pratama; M. Andriansah; Yadi Budiman; Lili Halimah (JURNAL PENDIDIKAN IPS, 2025)
This study aims to examine the quality of life within traditional communities in West Java by highlighting the role of local wisdom as the main framework shaping social, cultural, economic, and environmental well-being. The research focuses on three traditional villages: Kampung Pulo in Garut, Kampung Naga in Tasikmalaya, and Kampung Kuta in Ciamis. A qualitative approach was employed, using data collection techniques such as observation, in-depth interviews, and document analysis. The findings reveal that despite limited access to modernization, the quality of life in these communities remains preserved through local wisdom values such as mutual cooperation, environmental preservation, social solidarity, and adherence to customary norms. Local wisdom serves as a strong social capital that sustains the communities in a sustainable manner. This study recommends the protection and empowerment of indigenous communities as an essential part of fair and sustainable development efforts.